Dissociation of blood interleukin spectrum in the patients with accelerated aging and diabetic retinopathy - N. M. Agarkov; I. V. Lev; E. A. Voronina (Медицинская иммунология, 2024)
Diabetic retinopathy is a common complication of diabetes mellitus, especially, in elderly persons, due to growth of this population in many countries. However, involvement of immune system in patients with diabetic retinopathy and into the aging process is not sufficiently covered in the research works. The aim of the present study was to evaluate the contents of systemic interleukins in the patients with diabetic retinopathy with accelerated versus physiological aging.We observed 240 patients aged 60-74 years with diabetic retinopathy and 115 age-matched patients without diabetic retinopathy under clinical conditions. The diagnosis of diabetic retinopathy was assessed in accordance with Clinical Guidelines of the All-Russian Association of Ophthalmologists “Diagnostics and Treatment of Diabetic Retinopathy and Diabetic Macular Edema”. The biological age of the subjects was determined instrumentally, by means of VaSera VS-1500 sphygmomanometer. The contents of interleukins in blood plasma was determined by ELISA technique using the “Protein contour” kit.It was established that the chronological (calendar) age of patients with diabetic retinopathy and without diabetic retinopathy was not significantly different (70.9±0.7 and 70.2±0.8 years old, respectively; p > 0.05). However, the biological age in these groups differed significantly (75.7±1.1 and 72.3±1.0 years old, respectively; p < 0.001), thus suggesting accelerated aging of patients suffering from diabetic retinopathy. Plasma concentrations of interleukins in patients with diabetic retinopathy with accelerated aging, when compared with physiologically aged patients with diabetic retinopathy revealed statistically significant differences for the most analyzed interleukins. A particularly pronounced increase of the blood plasma interleukins in patients with diabetic retinopathy and accelerated aging was revealed for IL-6 (25.7±1.8 pg/mL versus 4.2±0.5 pg/mL in physiologically aged patients with diabetic retinopathy (p < 0.001). A significant increase of interleukin levels among patients with accelerated aging and diabetic retinopathy was found for IL-13 and IL-17. IL-13 contents in the patients with diabetic retinopathy and accelerated aging reached 2.2±0.3 pg/mL versus 0.7±0.2 pg/mL in physiologically aging patients with diabetic retinopathy (p < 0.001). Respectively, the IL-17 levels were 19.8±0.6 pg/mL and 8.4±0.9 pg/mL. The mean concentration of IL-1b, IL-3 among patients with diabetic retinopathy and accelerated aging was also significantly increased. At the same time, in the blood plasma of the prematurely aged patients with diabetic retinopathy, we have revealed a statistically significant decrease of anti-inflammatory interleukins and, especially, IL-10 to 7.4±0.6 pg/mL versus 19.2±0.7 pg/mL (p < 0.001). Therefore, IL-6, IL-8, IL-13, IL-17, IL-4, and IL-10 levels may be used as immunological predictors of accelerated aging in the patients with diabetic retinopathy.